2004
DOI: 10.1002/meet.1450410117
|View full text |Cite
|
Sign up to set email alerts
|

A case study of communication channels in a graduate program

Abstract: The investigators attempt to obtain a thorough understanding of the communication channels used in a graduate program, which is an independent academic unit. After collecting data with qualitative and quantitative research methods, the investigators analyze and present the findings regarding four major aspects: (1) the current communication channels used in the program; (2) how the students, faculty and staff perceived the communication methods utilized; (3) the relationship between students' viewpoints and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, Spennenmann 2007in a recent study of Internet usage by nine Australian universities (students, administrators and academics) found that the majority of users (81 per cent) used the service between the standard office hours of 8.00 and 5.00 with another slight peak after dinner (7.00 p.m.). Huang, Chen & Chen (2004) in carrying out a study of communication channels used in a graduate program at an American university asked students how often they checked their E-mail accounts and the school Website. The researchers found that 96.25% of participants checked their Emails at least once a day, where 83.75% visited the school Website at least once a week.…”
Section: What Others Have Foundmentioning
confidence: 99%
“…Interestingly, Spennenmann 2007in a recent study of Internet usage by nine Australian universities (students, administrators and academics) found that the majority of users (81 per cent) used the service between the standard office hours of 8.00 and 5.00 with another slight peak after dinner (7.00 p.m.). Huang, Chen & Chen (2004) in carrying out a study of communication channels used in a graduate program at an American university asked students how often they checked their E-mail accounts and the school Website. The researchers found that 96.25% of participants checked their Emails at least once a day, where 83.75% visited the school Website at least once a week.…”
Section: What Others Have Foundmentioning
confidence: 99%